2015
DOI: 10.1097/prs.0000000000001531
|View full text |Cite
|
Sign up to set email alerts
|

Are Quantitative Measures of Academic Productivity Correlated with Academic Rank in Plastic Surgery? A National Study

Abstract: Academic rank in plastic surgery is strongly correlated with several quantitative metrics of research productivity. Although academic promotion is the result of success in multiple different areas, bibliometric measures may be useful adjuncts for assessment of research productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools.…”
Section: Resultsmentioning
confidence: 99%
“…20 Studies in the medical literature have yielded significant results, albeit with higher thresholds for promotion. Among oral and maxillofacial surgeons and plastic and reconstructive surgeons, a recent study found that the h-index was strongly correlated with academic rank (r=0.62-0.64, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A 10 unit increase, on average, was shown to be the difference between full professors and assistant professors in plastic surgery residency training programs (2932). The driver behind the strong association between having a higher h-index and receiving greater payments from industry is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, academic productivity was measured by utilizing the h-index. Although the efficacy of the h-index in assessing academic productivity has been validated in several medical specialties, including plastic surgery (30, 32, 35), it has several limitations which are beyond the discussion of this paper. Moreover, the availability of OPP data is limited to a 5-month reporting period, which may not give a true picture of the entire physician-industry financial landscape.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 For example, if an author has published 20 papers, and 12 of those papers have at least 12 citations (ie, the author's 13th paper has less than 13 citations), an author has an h-index of 12. Despite the fact that it was originally introduced in the physical sciences, recent studies in multiple specialties in academic medicine have validated the h-index, including radiology, 3,8 radiation oncology, 9 emergency medicine, 10 anesthesiology, [11][12][13] otolaryngology, 4,14,15 neurosurgery, 5,16 urology, 17 plastic surgery, 2,18,19 oral and maxillofacial surgery, 20 and hand surgery. 21 With literature continuing to support the use of the h-index in academic medicine, one must consider the influence of self-citation.…”
mentioning
confidence: 99%